Time as Exchange Value: Political Economy of Signs and Self–Other in Film “In Time” - Heryanto, Naldo Yanuar (ULTIMART Jurnal Komunikasi Visual, 2025)
This research analyzes how time is represented as exchange value in the science fiction film In Time (2011), through the combined lenses of Jean Baudrillard’s hyperreality, the political economy of signs, and Greimas’s semiotic square. The study departs from the premise that value in contemporary capitalism is increasingly tied to symbolic representation rather than material production. Through visual discourse analysis and Greimasian semiotics, this study exposes how colors, narrative structure, and character transformation function to encode subject–other relations, reinforcing class divisions. The film depicts a hyperreal capitalist system where time is commodified, converting human lifespan into currency and creating stark divisions between dominant and marginalized classes. This alignment with Marxist critique shows how capitalism extracts value from human life itself. In contrast with Indonesian cultural contexts where time holds relational and cyclical significance rather than exchangeable value, the film illustrates a radical commodification of time. In conclusion, the film not only visualizes socio-economic inequality but uses speculative narratives to critique capitalist logics embedded in contemporary visual culture. Future research is encouraged to explore how symbolic objects and semiotic structures in popular media function as ideological apparatuses in the hyperreal age.